PENGESAHAN AKTA DI BAWAH TANGAN OLEH NOTARIS - Tazzani, Sakduddin Ataf ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Notary is a public official under the provisions of Article 15 paragraph (2) letter a of Law Number 30 Year 2004 concerning Notary Position (UUJN) is authorized to certify signatures and establish certainty under the hand of a letter dated by enrolling in a special book (legalisasi). Based on this research aims to find out why there needs to be approved of the legalization unauthentic deed (legalisasi) by Notary and also to find out how the responsibilities of the parties to the legalization unauthentic deed was doing. The research method used in this research is normative juridical or legal research literature, which examines the principles and legal norms relating to the legalization unauthentic deed by a notary as a public official. normative legal research is basically focused on the use of book study or library materials in the excavation of research material. The results obtained show that legalization unauthentic deed which was passed by the Notary (legalisasi) is required to ensure the certainty of the date and signature of the parties in deed it is true that party's signature contained in the deed, so that legalization unauthentic deed by a notary can be used as evidence for the parties in a civil case in court. To the deed unauthentic which was passed by the Deed, the parties will be difficult to refute or deny the signature as well say do not know its contents, because before signed by the parties before a Notary has been read and explained the contents and purpose of such deed. If the implementation is a violation of those provisions to the legalization or a distortion of the authority and the obligations and restrictions set by UUJN, then the notary can be sued legally accountable, that is civil liability, criminal, administrative accountability, and ethical accountability. Accountability of the parties to the legalization deed is to provide real information about the identity and other information necessary to the Notary as well as providing a service fee as a fee to the Notary.